Evaluation of Genistein’s Cytotoxic and Apoptotic Effects on Human Foreskin Fibroblasts: A Molecular and Biochemical Analysis: Effects of Genistein on Fibroblast cells - Pourmohammad, Mohammadreza; Khayatzadeh , Jina; Talaei, Somaye; Molavi, Farahnaz (Iranian Journal of Pharmaceutical Sciences, 2025)
Genistein, a naturally occurring isoflavone in soybeans, has gained attention for its phytoestrogenic and antioxidant properties. Its role in endocrine modulation, oxidative stress regulation, and apoptosis suggests therapeutic potential in cancer and metabolic disorders. Foreskin fibroblasts serve as a model for studying genistein’s effects on cell proliferation, oxidative stress, and cytotoxicity. This study examines genistein’s influence on gene expression related to cell growth and stress responses, offering insights into its therapeutic or adverse effects. Human foreskin samples from seven donors (6–12 years old) were used. Fibroblasts were isolated via collagenase and trypsin digestion and cultured in DMEM with 10% FBS. Cells were treated with genistein (20–100 µM), and viability was assessed using MTT assays. Antioxidant enzyme activities (SOD, GPx, CAT) were quantified spectrophotometrically. Gene expression of Bax, Bcl-2, IGF-1, and Casp3 was analyzed via real-time PCR. Data were evaluated using t-tests and ANOVA, with p<0.05 considered significant. Genistein induced dose- and time-dependent cytotoxicity, significantly reducing cell survival above 40 µM. IC50 values decreased over time, confirming enhanced cytotoxicity. Enzyme activity assays showed reduced CAT, SOD, and GPx levels. Gene analysis revealed upregulation of pro-apoptotic markers (BAX, Casp3) and downregulation of anti-apoptotic genes (Bcl-2, IGF-1), with a BAX/Bcl-2 ratio exceeding one, indicating apoptosis. These findings highlight genistein’s potential as a therapeutic agent via oxidative stress modulation and apoptosis induction. This study confirms genistein’s cytotoxic effects on fibroblast cells through oxidative stress and apoptosis. Further research is needed to clarify its molecular mechanisms and optimize therapeutic applications.